Biosynthesis of the antimicrobial cyclic lipopeptides nunamycin and nunapeptin by Pseudomonas fluorescens strain In5 is regulated by the LuxR‐type transcriptional regulator NunF. Issue 6 (6th August 2017) - Hennessy, Rosanna C.; Phippen, Christopher B. W.; Nielsen, Kristian F.; Olsson, Stefan; Stougaard, Peter
Abstract: Nunamycin and nunapeptin are two antimicrobial cyclic lipopeptides (CLPs) produced by Pseudomonas fluorescens In5 and synthesized by nonribosomal synthetases (NRPS) located on two gene clusters designated the nun–nup regulon. Organization of the regulon is similar to clusters found in other CLP‐producing pseudomonads except for the border regions where putative LuxR‐type regulators are located. This study focuses on understanding the regulatory role of the LuxR‐type‐encoding gene nunF in CLP production of P. fluorescens In5. Functional analysis of nunF coupled with liquid chromatography–high‐resolution mass spectrometry (LC‐HRMS) showed that CLP biosynthesis is regulated by nunF . Quantitative real‐time PCR analysis indicated that transcription of the NRPS genes catalyzing CLP production is strongly reduced when nunF is mutated indicating that nunF is part of the nun–nup regulon. Swarming and biofilm formation was reduced in a nunF knockout mutant suggesting that these CLPs may also play a role in these phenomena as observed in other pseudomonads. Fusion of the nunF promoter region to mCherry showed that nunF is strongly upregulated in response to carbon sources indicating the presence of a fungus suggesting that environmental elicitors may also influence nunF expression which upon activation regulates nunamycin and nunapeptin production required for the growth inhibition of phytopathogens. Abstract : Role of LuxR‐type regulator in the synthesis of two antifungal secondary metabolites nunamycin and nunapeptin in the Greenlandic isolate P. fluorescens In5.